La confianza en la SUNAT y su relación con la recaudación tributaria en Loreto, año 2019 - Aguilar Shapiama, Santiago Fernando (2023)
This research examined the relationship between tax revenue and institutional trust in the Loreto department during the period 2019. The results supported the hypothesis that there is a direct relationship between both variables, indicating that higher levels of trust in the SUNAT are associated with an increase in tax revenue. Additionally, a positive relationship was found between the effectiveness of control and auditing by the SUNAT and the level of service to taxpayers. It was also confirmed that there is an inverse relationship between tax evasion and trust in the tax system. These findings support the importance of strengthening tax institutions, improving tax administration, promoting transparency, and combating corruption. Recommendations include enhancing the effectiveness of control and auditing, facilitating tax compliance, promoting transparency, and establishing strategic alliances. In conclusion, strengthening institutional trust and fostering a culture of tax compliance will contribute to more effective tax revenue collection and the economic and social development of the Loreto department.